(untitled) (International Journal of Food and Nutritional Sciences, 2022)
There has been a noticeable increase in the demand for petroleum products all across the world. Vehicle traffic continues to increase daily. As the global population has increased in recent years, so too has the number of cars on the road. Increases in the number of cars on the road have coincided with a corresponding increase in demand for fossil fuels like petrol and diesel. Because of this, vegetable oil has the potential to be a convenient replacement fuel for already-existing diesel automobiles. Therefore, in order to fill these needs, individuals will have to research alternatives to traditional fossil fuels such as petrol and diesel. Non-edible oils, such as honge oil blend, were the only focus of this article because they can be used as fuel for C.I. engines. The main purpose of this study is to compare the efficiency and pollution levels of a multi-cylinder, constant-speed diesel engine running on an honge oil blend and a diesel fuel. There was only a quick inspection of the tools and materials before we got started with the experiment. All of the measured data has been analysed and calculated. The thermal efficiency, specific fuel consumption, and emissions of a diesel and honge oil brake system were measured from no load to full load using a four stroke multicylinder diesel engine.